ANALYSIS OF CLINICAL PROFILE, AETIOLOGY, CLASSIFICATION AND OUTCOME OF INTERSTITIAL LUNG DISEASES AT A SINGLE CENTER OF SRI LANKA- A DESCRIPTIVE STUDY - Madegedara, Dushantha; Rathnayake, Saman; Bandara, Asela (International Journal of Research -GRANTHAALAYAH, 2020)
Background: Interstitial lung diseases (ILD) comprise a diverse group of heterogeneous entities. Epidemiology, clinical profile and prognosis of interstitial lung diseases widely vary globally. Little data are available on ILD in Sri Lanka. Objective and methodology: A single center descriptive study conducted at Teaching hospital-Kandy, Sri Lanka among diagnosed ILD patients from 2007-2018. Demographic, clinical and radiological data were collected retrospectively to analyse clinical profile, aetiology, classification and outcome of interstitial lung diseases. Results: 302 subjects were analyzed (mean age 59.5 years, female 61.3%). Idiopathic interstitial pneumonias (IIP) were the commonest (42.3%, N=128) followed by secondary ILD due to known aetiologies(40.7%, N=123), hypersensitivity pneumonitis (14.6%, N=44) and sarcoidosis (2%, N=6). Majority of IIPs were nonspecific interstitial pneumonia (NSIP)(46.8%, N=60), followed by idiopathic pulmonary fibrosis (IPF)(28.1%, N=36). Majority of secondary ILDs were due to connective tissue diseases (87%, N= 107). Shortness of breath and cough were the commonest presenting symptoms, found in 271 (90.3%) and 250 (83.3%) patients respectively. High resolutions computerized tomography (HRCT) was performed in all, but histology was available in 54 (17.8%). Lung functions tests (LFT) were normal in 71 (26.3%), but demonstrated restrictive pattern in 182 (67.4%). Mean percentage predicated forced vital capacity (FVC) was 66.91 ± 18.7% while mean percentage predicted forced expiratory volume at 01 second (FEV1) was 69.92 ± 20.0%. Therewas no significant change in LFT during follow up. Infective exacerbations needing hospitalization was the commonest complication seen in 86 (40.3%). Data on follow up radiological investigations were noted in 143 (47.5%), in which 59 (41.2%) demonstrated radiological improvement, while 34 (23.7%) had progressive changes and 50 (34.9%) had HRCT changes similar to previous images. 184 patients were found surviving, while 43 were dead. Higher mean age, male gender, current or previous smoking, lower distance achieved at 6-minute walking test, or any history of hospitalizations due to infective exacerbations were noted to be associated significantly in patients with mortality. Conclusion: IIP and secondary ILDs were similar in prevalence in the cohort of diagnosed ILD patients from central Sri Lanka. Idiopathic NSIP outnumbered IPF in the sample.